The Effectiveness of Video-Based Health Education in Improving Adolescents’ Awareness of Premarital Sexual Behavior - Rahmadyanti; Kartiwi; Apriyanti; Fevi Febriyanti; Linda Fitriyani (Jurnal Penelitian Pendidikan IPA, 2025)
Premarital sexual behavior among adolescents remains a significant public health concern globally and in Indonesia. The World Health Organization (2022) reported that approximately 16 million girls aged 15–19 give birth each year, with the highest proportion occurring in developing countries. In Indonesia, the National Population and Family Planning Agency (BKKBN) have documented a rise in unintended pregnancies among adolescents, which is strongly associated with limited sexual health knowledge and low awareness of the risks associated with premarital sexual behavior. This study aimed to examine the effectiveness of video-based health education in improving adolescents’ awareness of premarital sexual behavior. This quasi-experimental study involved all 9th-grade students (n = 282) using a total sampling technique. Data analysis was performed using SPSS. Normality testing was conducted prior to hypothesis testing. A paired sample t-test was used for normally distributed data, while the Wilcoxon signed-rank test was used for non-normally distributed data. The Wilcoxon signed-rank test showed a significant difference in adolescents’ knowledge and attitudes regarding premarital sexual behavior after the intervention (Asymp. Sig. (2-tailed) = 0.000). Since p < 0.05, the hypothesis is accepted. These findings indicate that video-based health education is effective in increasing adolescents’ awareness of premarital sexual behavior. Video-based health education significantly improves adolescents’ knowledge and attitudes regarding the risks of premarital sexual activity and represents an effective strategy for school-based sexual health promotion.